The Relationship between Implicit and Explicit Attitudes of Nursing Students Toward Persons with Intellectual Disabilities According to Islamic Review - Rika Amelia; Karimulloh, Karimulloh (Pascasarjana IAIN Sultan Amai Gorontalo, 2025)
People with intellectual disabilities are a minority of individuals certainly have various kinds of problems in their social environment. These problems arise due to the stigma that has been embedded and developed in society towards people with intellectual disabilities. The stigma that grows in society affects a person's attitude, especially health workers, both consciously (explicit) and unconsciously (implicit). It is important for the community, especially health workers, to have positive implicit and explicit attitudes because both attitudes can influence their intervention behavior towards people with intellectual disabilities. Islam always teaches its followers to be positive to Allah and other fellow humans. This study aims to find out how the relationship between implicit and explicit attitudes of nursing students toward people with intellectual disabilities is according to Islamic review. The research method used is a literature review by searching and analyzing several primary references from the Quran and hadith, as well as other supporting references, both from journals, articles, and relevant books. The results of this study indicate that explicit attitudes are concluded to be negatively related and implicit attitudes are positively related.